2016
DOI: 10.1037/apl0000124
|View full text |Cite
|
Sign up to set email alerts
|

The struggle with employee engagement: Measures and construct clarification using five samples.

Abstract: Among scholarly researchers, the Utrecht Work Engagement Scale (UWES) is a popular scale for assessing employee or work engagement. However, challenges to the scale's validity have raised major concerns about the measurement and conceptualization of engagement as a construct. Across 4 field samples, we examined 2 measures of engagement, the UWES and the Job Engagement Scale (JES), in both factor structure and patterns of relationships with theoretically hypothesized antecedents and consequences. In a fifth fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(134 citation statements)
references
References 102 publications
(218 reference statements)
3
114
1
2
Order By: Relevance
“…First, in line with earlier research showing internal consistency reliability of the JES ranged from 0.88 to 0.96 (e.g., Alfes et al, 2012;Basit & Arshad, 2016;Byrne et al, 2016;Chen et al, 2014;He et al, 2013;Rich et al, 2010;Shuck et al, 2014), the JES in the present study showed excellent internal consistency reliabilities well above the cutoff criteria of 0.70 (Nunnally & Bernstein, 1994) for both Pakistan (α = 0.97) and Malaysia (α = 0.95).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…First, in line with earlier research showing internal consistency reliability of the JES ranged from 0.88 to 0.96 (e.g., Alfes et al, 2012;Basit & Arshad, 2016;Byrne et al, 2016;Chen et al, 2014;He et al, 2013;Rich et al, 2010;Shuck et al, 2014), the JES in the present study showed excellent internal consistency reliabilities well above the cutoff criteria of 0.70 (Nunnally & Bernstein, 1994) for both Pakistan (α = 0.97) and Malaysia (α = 0.95).…”
Section: Discussionsupporting
confidence: 75%
“…For instance, Saks and Gruman (2014) in their literature review have noted that as compared to Schaufeli et al (2002)'s view, Kahn's (1990) definition of engagement is relatively precise and grounded better in theory. In a similar vein, Byrne et al (2016) have examined the measures of engagement across five field samples and found that both the UWES and JES showed strong correlation but were not interchangeable. The authors concluded that because these scales measure different aspects of engagement, the UWES is more suitable in applied settings and the JES should be preferred in research settings.…”
Section: Importance Of the Job Engagement Scale In Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Construct clarity is critical not only for building new theory (Suddaby, 2010) but also for developing measures, measurements and manipulations of constructs (Byrne et al, 2016), as well as for comparing, aggregating and replicating empirical studies (Fisher and Aguinis, 2017;Le et al, 2010). Therefore, a review can contribute to and advance theory by clarifying a construct.…”
Section: Clarifying Constructs In Review Papersmentioning
confidence: 99%
“…This focus on stability and self-employment has been criticized, particularly by HRD and management scholars, as being less substantial and less meaningful than personal role engagement (Cole, Walter, Bedeian, & O ' Boyle, 2012 ;Fletcher, 2016 ;Saks & Gruman, 2014 ). This is because work engagement seems to (a) overlap too much with the concept and construct of burnout and other work attitudes, whereas personal role engagement is considered a more distinct motivational concept (Byrne, Peters, & Weston, 2016 ;Cole et al, 2012 ;Saks & Gruman, 2014 ); (b) focus more narrowly on transactional elements of work activities more so than personal role engagement, which focuses on a broader set of situationally and organizationally embedded elements of work roles (Bargagliotti, 2012 ;Fletcher, 2016 ); and (c) neglect to fully incorporate the role of personal agency and authenticity of self-expression, whereas personal role engagement emphasizes both employment and expression of the self (Kahn & Heaphy, 2014 ;Saks & Gruman, 2014 ).…”
mentioning
confidence: 99%